Implementasi Sistem Monitoring Absensi Berbasis Rfid Proxymity - Muhtajuddin Danny (Teknik Informatika, Universitas Pelita Bangsa, 2020)
The fact is that there are still many companies that use manual attendance records, that is, by using an attendance record at the time of entry and completion of work time. Reducing efficiency and company accuracy in optimizing their productivity This final project aims to design a prototype of an RFID attendance system that is integrated with a database to support the employee disciplinary attitude improvement program as the first step in improving the overall work performance of the company. This prototype RFID attendance system consists of several main components, namely tags that will be used as a substitute for ID cards and readers that are used to read information regarding employee attendance, database integration in this system will allow data to be stored automatically into the database. The result of this final project is a prototype of an RFID attendance system that has a function to store employee attendance data, with a maximum reading distance of 2 cm with a chance of success of 1 and a minimum reading interval of 2 seconds to perform its function optimally. Keywords: RFID, absence, otomatically